A male (15;15) Robertsonian translocation case with 11 previous consecutive recurrent spontaneous abortions - (:unkn) unknown (My University, 2004)
Robertsonian translocation is one of the major chromosomal re-arrangements and constitutes 18% of all genetic abnormalities with an incidence of 1/1000 in the general population. Re-arrangements between homologous chromosomes are very rare and mainly manifest as monosomic or trisomic offspring. A couple was referred to our center with a history of eleven consecutive spontaneous abortions. The father was diagnosed as having 15;15 Robertsonian translocation. Fluorescence in situ hybridization analysis (FISH) was applied on sperm cells and resulted in only nullisomy and disomy for chromosome 15 that leads to monosomy or trisomy 15 in case fertilization occurs. Therefore the couple was counselled extensively on the risk of a future pregnancy. Furthermore they were informed that they would not benefit from preimplantation genetic diagnosis and sperm donation and adoption could be the only solution.
Keywords: Homologous Robertsonian translocation; Recurrent abortion; Sperm FISH